2018
DOI: 10.3832/ifor2855-011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silver and copper nanoparticles on the growth and mycorrhizal colonisation of Scots pine (Pinus sylvestris L.) in a container nursery experiment

Abstract: Recent research points to the possibility of nanoparticles being used as fertilisers, growth stimulators, and promoters of plant resistance or pesticides. In this study, we sought to determine the influence of nanoparticles of silver and copper (AgNPs and CuNPs) on growth parameters and spontaneous mycorrhizal colonisation of roots in 2-year-old container-grown seedlings of Scots pine. Foliar applications of nanoparticles were made through two growing seasons, four times a season, at concentrations of 0, 5, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Previously, the influence of NPs has mainly been researched by reference to crop plants, with only a few studies devoted to woody species. The results of the latter have furthermore been very varied-encompassing stimulation of growth [30] and the lack of any influence [40][41][42], through to inhibition [43]. In contrast, our work points to a differentiated influence of NPs, depending on both plant species and type of nanomaterial.…”
Section: Discussionmentioning
confidence: 77%
“…Previously, the influence of NPs has mainly been researched by reference to crop plants, with only a few studies devoted to woody species. The results of the latter have furthermore been very varied-encompassing stimulation of growth [30] and the lack of any influence [40][41][42], through to inhibition [43]. In contrast, our work points to a differentiated influence of NPs, depending on both plant species and type of nanomaterial.…”
Section: Discussionmentioning
confidence: 77%
“…Nanoparticles were applied to leaves four times over the course of two growth seasons, at concentrations of 0, 5, 25, and 50 ppm. At all doses, the applied Cu-NPs promoted mycorrhizal colonization (Aleksandrowicz-Trzcinska et al 2018). Fe-NPs and Cu-NPs solutions were applied to Scots pine seeds in a laboratory setting to increase their seeding properties and significantly lower the likelihood of mold damage to the seedlings (Polischuk et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In general terms, the foliar applications did not reduce the ectomycorrhizal infection. In concentrations of 25 ppm, both ENPs showed a higher degree of mycorrhization, being a value of 37.1% for Cu- and 37.5% in Ag-ENPs (Aleksandrowicz-Trzcinska et al, 2018 ). Another study reported that carbon and nitrogen concentrations were not affected concerning microbial biomass; moreover, the C/N ectomycorrhizae ratio was directly affected by the increase in levels of Fe3O 4 - and SnO 2 -ENPs (Antisari et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%